Molecular characterization of the 17D-204 yellow fever vaccine. Issue 41 (5th October 2015) - Salmona, Maud; Gazaignes, Sandrine; Mercier-Delarue, Severine; Garnier, Fabienne; Korimbocus, Jehanara; Colin de Verdière, Nathalie; LeGoff, Jerome; Roques, Pierre; Simon, François
Abstract: Introduction: The worldwide use of yellow fever (YF) live attenuated vaccines came recently under close scrutiny as rare but serious adverse events have been reported. The population identified at major risk for these safety issues were extreme ages and immunocompromised subjects. StudyNCT01426243 conducted by the French National Agency for AIDS research is an ongoing interventional study to evaluate the safety of the vaccine and the specific immune responses in HIV-infected patients following 17D-204 vaccination. As a preliminary study, we characterized the molecular diversity from E gene of the single 17D-204 vaccine batch used in this clinical study. Materials and methods: Eight vials of lyophilized 17D-204 vaccine (Stamaril ®, Sanofi-Pasteur, Lyon, France) of the E5499 batch were reconstituted for viral quantification, cloning and sequencing of C/prM/E region. Results: The average rate of virions per vial was 8.68 ± 0.07 log10 genome equivalents with a low coefficient of variation (0.81%). 246 sequences of the C/prM/E region (29–33 per vials) were generated and analyzed for the eight vials, 25 (10%) being defective and excluded from analyses. 95% of sequences had at least one nucleotide mutation. The mutations were observed on 662 variant sites distributed through all over the 1995 nucleotides sequence and were mainly non-synonymous (66%). Genome variability between vaccine vials was highly homogeneous with a nucleotide distance ranging from 0.29% to 0.41%. Average p -distances observed for each vial were also homogeneous, ranging from 0.15% to 0.31%. Conclusion: This study showed a homogenous YF virus RNA quantity in vaccine vials within a single lot and a low clonal diversity inter and intra vaccine vials. These results are consistent with a recent study showing that the main mechanism of attenuation resulted in the loss of diversity in the YF virus quasi-species.